Using conformity control of concrete compressive strength for construction site classification - Cunha, P. J. (2013)
The accomplishment of the required strength class in concrete design is very important to avoid the development of pathologies into the concrete structures. This paper intends to evaluate the design required and the obtained strength classes of the concretes produced in ten different construction sites located in the north of Portugal. The strength classes were determined testing standard specimens. In order to know the in-situ compressive strength, cores were also extracted and tested. It was found that the in-situ compressive strength classes were higher than the obtained through the standard moulded specimens. These unexpected results can be explained due to a lack of knowledge and inspection on the manufacture of the specimens. The more extensive, fast and tight is the inspection, the better the control and the corrections in time, in order to maintain the quality of concrete used. It is important for a proper awareness, a training of the persons involved in this matter. Considering all the results obtained a construction site coefficient is proposed in order to classify the construction sites.